2021
DOI: 10.3390/molecules26133951
|View full text |Cite
|
Sign up to set email alerts
|

Brain Long Noncoding RNAs: Multitask Regulators of Neuronal Differentiation and Function

Abstract: The extraordinary cellular diversity and the complex connections established within different cells types render the nervous system of vertebrates one of the most sophisticated tissues found in living organisms. Such complexity is ensured by numerous regulatory mechanisms that provide tight spatiotemporal control, robustness and reliability. While the unusual abundance of long noncoding RNAs (lncRNAs) in nervous tissues was traditionally puzzling, it is becoming clear that these molecules have genuine regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 221 publications
0
3
0
Order By: Relevance
“…During this cell cycle remodeling process triggered by the regulatory effects of CREB1 and JNK, environmental signaling for neurogenesis could be released. With the continuation of induction, the existence of an intermediate state allows the activation of neural development and damage repaired-related genes (NEAT1, MALAT1, ADARB1, NRG1, ZBTB20, PURA) [35][36][37][38][39][40]. The successful and continuous expression of the above intermediate state-related genes may provide the basis for successful FiNs reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…During this cell cycle remodeling process triggered by the regulatory effects of CREB1 and JNK, environmental signaling for neurogenesis could be released. With the continuation of induction, the existence of an intermediate state allows the activation of neural development and damage repaired-related genes (NEAT1, MALAT1, ADARB1, NRG1, ZBTB20, PURA) [35][36][37][38][39][40]. The successful and continuous expression of the above intermediate state-related genes may provide the basis for successful FiNs reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, this study was limited to protein coding genes and future work should include similar analyses on noncoding RNA (ncRNA) expression, such as microRNAs and long noncoding RNAs, as previous studies have shown that such RNAs are expressed in a tissue- and cell-specific manner, involved in neuronal differentiation and function, and implicated in various brain disorders. 88 - 95 However, although databases providing information on ncRNAs along with tissue expression profiles and predicted functions are now available as well as ncRNA knockout mouse models with reported phenotypes, 96 - 101 there is still a lack of databases that compiles the results from mutational studies and which also links the ncRNAs to phenotype in a similar way as the MGI’s Mammalian Phenotype database. Such databases would be of high value when further studying the roles of hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Regulatory RNAs, that include but are not limited to, long non-coding RNAs (lncRNA), microRNAs (miRNA) and circular RNAs (circRNAs), play crucial roles in various biological processes ranging from cell survival to specialized functions like target innervation. Such RNA species are often subjected to modifications, post-transcriptional processing, and are localized to different subcellular compartments, all of which contribute to their biological activity and specificity (Sambandan, 2017 ; Rajgor, 2020 ; Keihani et al, 2021 ; Samaddar and Banerjee, 2021 ; Zajaczkowski and Bredy, 2021 ). Lastly, mRNAs or their non-coding portions such as untranslated regions (UTRs) and introns can be bestowed with alternative functions independent of their coding potential and have been shown to modulate protein-protein interactions, intracellular signaling, subcellular localization and time-dependent expression (Nam et al, 2016 ; Andreassi et al, 2018 ; Huang, 2021 ).…”
mentioning
confidence: 99%